Argumentation and strategies of persuation and conviction in Quranic discourse - benattia, mustapha; zehar, mohammed (El Omda in Linguistics and Discourse Analysis, 2023)
Argumentation is considered to be one of the procedural tools and one of the most important types of texts contributing to the success of the linguistic communication process which, in turn, relies on several means of expression and forms of discourse such as dialogue, persuasion, demonstration, and deduction. We find mention of this research theme in several writings of the Arabic and Western language heritage but contemporary studies have further enriched it by highlighting in particular dialectics, oratory, methods of argumentation, and deduction. Based on the premise that language is a medium of communication, rhetoricians have treated argumentation as an assertoric style by proposing ideas and demonstrating their truthfulness. By analyzing several dialogues taken from the Holy Quran, we try, in this study, to highlight the most effective methods of demonstration and argument